PERAN DAN STRATEGI HUMAS DALAM MENINGKATKAN CITRA POSITIF TAMAN BALEKAMBANG DI MASYARAKAT KOTA SOLO - Sari, Dhika Novita (KOMUNITAS, 2014)
The  Role  of  public  relations  as  an  agency  is  very  crucial.  It  is  due  to  the  fact  that  if  the  problems  appears dealing with the public so public relation has responsible to give understanding to them. Public Relation also has  a  very  important  role  in  conveying  an  understanding  related  to  the  information  of  the  company  to  the public. Therefore, the role and strategy of public  relations is very essential in improving the positive image of the company. This study aims to identify, to classify and to describe the role and strategy of Balekambang public relations in improving the positive image the Solo  community. This study belongs to qualitative research. This research uses Kusumastuti Frida (2002 ) and Ruslan  Rosad (2002 ) theories in the data analysis . The results shows  that  the  role  and  strategies  of  public  relations  is  success  in  improving  the  positive  image  of Balekambang.  The  role  of  public  relations  is  done  in  Balekambang,  namely  (1)  facilitator  of  communication covers receiving community complaints and facilitate communication with reporters, (2) facilitator of problems solving  process  by  classifying  the  problems  that  not  only  internal  but  also  external  of  Balekambang.  Then, provide  a  solution  by  doing  the  communications  between  related  parties,  (3)  communications  technician  in writing press releases deals with media. Meanwhile the strategies used by the Balekambang public relations are (1) holding event publications, (2) event strategy  is made in order to Balekambang more widely known by the public,  (3)  News  strategy  is  done  by  Balekambang  public  relation  by  always  makes  press  releases  about everything related to Balekambang, (4) community involvement strategy in Balekambang the public relations by holding social contact with certain communities in  order to maintain a good relationship, (5) inform or image strategy ( notify the image ) the task Balekambang public relation publishes Balekambang with holding positive events, (6) lobbying and negotiation strategy, Balekambang public realation lobbies and negotiates toward the parties  to  conduct  activities  /  events  that  can  give  benefit  both  them,  and  (7)  social  responsibility  strategy, Balekambang public relation held a social event.